Intranasal Analgesia and Sedation in Pediatric Emergency Care—A Prospective Observational Study on the Implementation of an Institutional Protocol in a Tertiary Children's Hospital. Issue 2 (February 2019) - Nemeth, Marcus; Jacobsen, Nils; Bantel, Carsten; Fieler, Melanie; Sümpelmann, Robert; Eich, Christoph
Abstract : Objectives: Children presenting with acute traumatic pain or in need of therapeutic or diagnostic procedures require rapid and effective analgesia and/or sedation. Intranasal administration (INA) promises to be a reliable, minimally invasive delivery route. However, INA is still underused in Germany. We hence developed a protocol for acute pain therapy (APT) and urgent analgesia and/or sedation (UAS). Our aim was to evaluate the effectiveness and safety of our protocol. Methods: We performed a prospective observational study in a tertiary children's hospital in Germany. Pediatric patients aged 0 to 17 years requiring APT or UAS were included. Fentanyl, s-ketamine, midazolam, or combinations were delivered according to protocol. Primary outcome variables included quality of analgesia and/or sedation as measured on age-appropriate scales and time to onset of drug action. Secondary outcomes were adverse events and serious adverse events. Results: One hundred pediatric patients aged 0.3 to 16 years were enrolled, 34 for APT and 66 for UAS. The median time onset of drug action was 5 minutes (ranging from 2 to 15 minutes). Fentanyl was most frequently used for APT (n = 19). Pain scores decreased by a median of 4 points (range, 0-10; P < 0.0001). For UAS, s-ketamine/midazolam was most frequently used (n = 25). Sedation score indicated minimal sedation in most cases. Overall success rate after the first attempt was 82%. Adverse events consisted of nasal burning (n = 2) and vomiting (n = 2). No serious adverse events were recorded. Conclusions: A fentanyl-, s-ketamine-, and midazolam-based INA protocol was effective and safe for APT and UAS. It should then be considered where intravenous access is impossible or inappropriate.